Patterns of Interactive Space Utilization in Public Facilities of Enrekang City Park: A Biophilic Design Approach Study - Izharul Haq; Hasniar Baharuddin; Nurhayati Kamaruddin (Journal Of Architectural Design & Technology, 2025)
Public spaces such as city parks play an important role in supporting social activities and community interactions. Taman Kota Enrekang is one of the green open spaces that is frequently used by various groups for recreational, educational, and community activities. This study aims to examine the usage patterns of interactive spaces in Taman Kota Enrekang through a biophilic design approach, which integrates natural elements to enhance the comfort and well-being of users. The research method used is descriptive qualitative with data collection techniques including field observations, interviews, and documentation. The results show that specific zones in the park, such as open seating areas, community stages, and nature literacy spaces, are more frequently used for gathering, discussions, and arts and educational activities. Biophilic elements such as lush vegetation, natural lighting, and water features contribute to user comfort and increase the duration and intensity of social interactions. These findings can serve as a basis for designing and developing public spaces that are responsive to the social and ecological needs of the community.